Pharmacokinetics of amrubicin in lung cancer patients with impaired hepatic function. (2016) - Ryuge, Shinichiro; Masuda, Noriyuki; Yamamoto, Nobuyuki; Takahashi, Toshiaki; Murakami, Haruyasu; Takeda, Koji; Daga, Haruko; Yonesaka, Kimio; Tsukuda, Hiroshi; Nakagawa, Kazuhiko; Tanaka, Kaoru; Kiura, Katsuyuki; et al.
Abstract: Objective: The pharmacokinetics of amrubicin in patients with impaired hepatic function have not been reported. The aim of this study was to compare the pharmacokinetics of amrubicin and its major metabolite, amrubicinol, and to assess the safety of amrubicin in lung cancer patients with impaired hepatic function and those with normal hepatic function. Materials and methods: Five patients with impaired hepatic function (arm I) and 10 patients with normal hepatic function (arm N) with small or non-small cell lung carcinoma were enrolled. Liquid chromatography with tandem mass spectrometry was used to determine the amrubicin and amrubicinol concentrations. Pharmacokinetic parameters were estimated by non-compartmental analysis. Results: The terminal half-lives of amrubicin and amrubicinol in whole blood and plasma were slightly longer in arm I than in arm N. The area under the concentration–time curve (AUC0–24h ) values of amrubicin in plasma and AUC0–120h of amrubicinol in whole blood in arm I were not larger than those in arm N because of dose adjustments based on prior treatment history and baseline values of total bilirubin, aspartate aminotransferase and alanine aminotransferase. The dose-normalized AUCs (dose 40 mg/m 2 ) of amrubicin and amrubicinol in arm I were slightly larger than those in arm N. There were two deaths in arm I, one related to disease progression and one from an unknown cause. Conclusion: If an adjusted dose of amrubicin is used in patients with impaired hepatic function, the exposure of amrubicin and amrubicinol would be within the range of variation observed in patients with normal hepatic function.